School types in adolescence and subsequent health and well-being in young adulthood: An outcome-wide analysis - Ying Chen (Public Library of Science (PLoS), 2021)
While past empirical studies have explored associations between types of primary and secondary schools and student academic achievement, outcomes beyond academic performance remain less well-understood. Using longitudinal data from a cohort of children (N = 12,288, mean age = 14.56 years) of nurses, this study examined associations between the types of schools participants attended in adolescence and a wide range of subsequent psychological well-being, social engagement, character strengths, mental health, health behavior and physical health outcomes. Results in this sample suggested little difference between attending private independent schools and public schools across outcomes in young adulthood. There were, however, notable differences in subsequent outcomes comparing homeschooling and public schools, and possibly some evidence comparing religious schools and public schools. Specifically, there was some evidence that attending religious schools versus public schools was associated with a higher likelihood of frequent religious service attendance and becoming registered voters, a lower risk of overweight/obese, fewer lifetime sexual partners, and a higher risk of subsequently being binge drinkers; however, these associations were not robust to correction for multiple testing. Homeschooling compared with public schooling was associated with subsequently more frequent volunteering (ß = 0.33, 95% CI = 0.15, 0.52), greater forgiveness (ß = 0.31, 95% CI = 0.16, 0.46), and more frequent religious service attendance (Risk Ratio [RR] = 1.51, 95% CI: 1.27, 1.80), and possibly also with greater purpose in life, less marijuana use, and fewer lifetime sexual partners, but negatively associated with college degree attainment (RR = 0.77, 95% CI: 0.67, 0.88) and possibly with greater risk of posttraumatic stress disorder. These results may encourage education stakeholders to consider a wider range of outcomes beyond academic performance in decision-making.